Dinamika Pelayanan pada Dinas Koperasi dan Usaha Mikro Kecil dan Menengah dan Perdagangan di Kabupaten Tegal - Wisnu Wisnu; Fatkhuri Fatkhuri (International Forum of Researchers and Lecturers, 2026)
This study examines the dynamics of public service delivery at the Office of Cooperatives, Small and Medium Enterprises, and Trade in Tegal Regency, focusing on its role in supporting local economic development. The background of this research is rooted in the increasing demand for effective, transparent, and responsive public services, particularly for cooperatives, micro, small, and medium enterprises (MSMEs), and the trade sector, which are key drivers of regional economic growth. The objective of this study is to analyze the quality and dynamics of services provided by the office, identify supporting and inhibiting factors, and assess their implications for service improvement. This research employs a qualitative descriptive method, using data collected through interviews, observations, and document analysis involving government officials and service users. The findings indicate that service delivery has shown positive developments through procedural improvements and service innovations; however, challenges remain in terms of human resource capacity, infrastructure limitations, and coordination mechanisms. These dynamics significantly influence the effectiveness of policy implementation and stakeholder satisfaction. The study implies that strengthening institutional capacity, enhancing digital-based services, and improving service professionalism are essential to achieving more optimal public service performance. The results of this research are expected to contribute to policy evaluation and serve as a reference for improving public service management in local government institutions, particularly in the cooperative, MSME, and trade sectors.